Research on Ease of Protective Clothing Based on Three-dimensional Human Body Scanning (Journal of Fiber Bioengineering and Informatics, 2019)
The experiment recruited 18 young healthy males as the subjects. Four postures with a limited range ofmovement during outdoor activity were captured by the mean of a 3D scanning system. The grids of rowsand columns were made on the skin surface before scanning. The grids’ distance in terms of skin stretchwas measured between the static posture and the four experimental postures. A paired sample T-testwas conducted to test that the variation in skin length change for each part of the body. Among them,there were more significant changes in the horizontal direction for the small shoulder width, back width,bust, hip, thigh circumference, knee circumference, big arm circumference and elbow circumference. Inthe vertical direction, except for the inner lines of the legs, all measured sizes changed significantly.Through further analysis, it was found that the back length and the back width were relatively activefactors that affected the entire upper limb movement. Finally, according to the changes in the measuredsizes, it is necessary to explore protective clothing in terms of ease.
Keywords: Protective Clothing; 3D Scanning System; Skin Stretch; Ease Design